2009
DOI: 10.1007/s00011-009-8116-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 administration attenuates pulmonary neutrophil infiltration and alters pulmonary iNOS activation following hemorrhagic shock

Abstract: These findings suggest that administration of IL-10 modulates the degree of hemorrhage-induced systemic and pulmonary inflammation and support the notion of a central role for iNOS in acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…In addition, recent studies have shown the protective role of IL-10 in hemorrhagic shock induced lung inflammation and injury [29,30]. Our results together with these data raise the possibility that one of the mechanisms of action of adenosine in protecting against lung injury is through augmenting IL-10 expression.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, recent studies have shown the protective role of IL-10 in hemorrhagic shock induced lung inflammation and injury [29,30]. Our results together with these data raise the possibility that one of the mechanisms of action of adenosine in protecting against lung injury is through augmenting IL-10 expression.…”
Section: Discussionsupporting
confidence: 75%
“…It should be noted in this context that administration of exogenous IL-10 or introduction of the IL-10 gene conferred protection against Pseudomonas aeruginosainduced (22) and bleomycin-induced lung injuries (23) in mice, as well as against immune complex-induced lung injury following intrapulmonary deposition of IgG or IgA in rats (24). Exogenous IL-10 administration was also found to attenuate lung injury following hemorrhagic shock (25).…”
Section: Discussionmentioning
confidence: 97%
“…These cells infiltrate to the tissue early after exposure, accumulate over time (17,26), and actively secrete damage mediators, such as neutrophil elastase, metalloproteinases, defensins, and reactive oxygen species (ROS), all of which induce and enhance tissue injury (27). Increased IL-10 levels were suggested to reduce lung neutrophil content (23,25). In the present study, a dramatic reduction in lung neutrophil content, almost by one-half at 72 h postexposure, was indeed observed in the ricinintoxicated group of mice treated with ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…2 Cell counts in the BAL of mice treated for 4 h. Total cell counts in the BAL were obtained from pelleted cells after lysis of red cells and staining with trypan blue and counting using a manual hemocytometer. The figure shows box-whisker graph with individual data points, boxes (25th to 75th percentiles of the data), whisker bars (5th to 95th percentiles), and mean (±1 SEM) of airway inflammation show that cytokines such as IL-10 and IL-12 can inhibit bronchial and alveolar inflammation [43,44] and neutrophil infiltration [45,46], and that high levels of RANTES decrease the activity of its receptor CCR5 and reduce inflammatory cell migration into inflammatory loci [47]. In the current study we found that AAT strongly enhances LPS-induced IL-10, IL-12, and RANTES levels in mice.…”
Section: Discussionmentioning
confidence: 99%